"Nothing in my years of community organizing has affected me as deeply as this closure did”: A critical exploration of the socio-spatial consequences of public-school closures in Ontario, Canada - Leger, Samantha; Collins, Patricia; Dean, Jennifer; Thompson, Carise (Canadian Planning and Policy / Aménagement et politique au Canada)

(untitled) (Association of Canadian University Planning Programs, 2023)
Public schools are more than educational institutions; they are public assets that have long proven essential parts of healthy, sustainable, and complete communities. Yet, public elementary schools are being permanently closed across Canada, particularly within urban and rural settings in Ontario; a trend that has important implications for socio-spatial equity and environmental justice in planned communities. The purpose of this paper is to explore the perceived impacts of elementary public-school closures for residents and communities using a mixed-methods approach including household surveys and in-depth interviews. The results indicated that, overwhelmingly, residents did not feel that they had the chance to meaningfully participate in the school closure process and that their voice was not heard throughout the engagement process. Further, the findings illuminated the lasting impacts of the school closure decision on the communities with physical, social, political, and economic outcomes in local neighbourhoods. The study illuminates the critical issue of responsible planning practice in understanding both the value of local community schools and local community input in ongoing pupil accommodation review processes.